Are tropical reptiles really declining? A six-year survey of snakes in a tropical coastal rainforest: role of prey and environment - Barquero González, José Pablo (2020)
Introduction: Even though snake declines seem to be a reality in many parts of the world, some reports are based on anecdotal evidence and there is a need of prolonged and intensive studies, especially in the tropics, for corroboration. Objective: To investigate if snake populations in Drake Bay are decreasing, and if there is a relationship with prey, time, temperature, rain and moonlight. Methods: We counted snakes seen per hour when walking along a single trail in the coastal forest of Drake Bay, Costa Rica. We walked the trail at night for a total of 842 nights (over 4 000 hours of observations), from 2012 through 2017 and recorded all the individual snakes we could see with head flashlights. We used ANOVA tests to check correlations among counts per hour with moonlight and rain; and graphic analysis for associations with diet, temperature, month and year. Results: We recorded 25 species (five families); which feed mostly on terrestrial vertebrates. Counts per hour have fallen over the years, especially for species that prey on amphibians and reptiles; Mastigodryas melanolomus has remained in similar numbers; and Siphlophis compressus has not been seen since May 2016. Temperature is relatively constant along the year in Drake, but month strongly affected the counts, which increased from August to September. Most species were seen more often in rainy nights (0.11 per hour versus only 0.03 per hour in nights without rain, ANOVA P < 0.05); we saw less Leptodeira septentrionalis on bright nights (0.12 per hour, versus 0.21 per hour in dark nights; ANOVA, P = 0.01), but all other species were unaffected by moonlight (ANOVA, P > 0.05). Conclusion: Night field counts of snakes in Drake Bay, Costa Rica, are not strongly affected by light or temperature, but are lower when there is no rain and show a strong decline from 2012 through 2017, particularly for species that feed on amphibians and reptiles. We have no reason to believe that the decline is an erroneous interpretation or that the snakes moved elsewhere, the decline of snakes in Drake seems to be real and needs attention from the conservation authorities.